Conformational Plasticity in Glycomimetics: Fluorocarbamethyl‐L‐idopyranosides Mimic the Intrinsic Dynamic Behaviour of Natural Idose Rings. Issue 29 (10th June 2015) - Unione, Luca; Xu, Bixue; Díaz, Dolores; Martín‐Santamaría, Sonsoles; Poveda, Ana; Sardinha, João; Rauter, Amelia Pilar; Blériot, Yves; Zhang, Yongmin; Cañada, F. Javier; Sollogoub, Matthieu; Jiménez‐Barbero, Jesus
Abstract Sugar function, structure and dynamics are intricately correlated. Ring flexibility is intrinsically related to biological activity; actually plasticity in L‐iduronic rings modulates their interactions with biological receptors. However, the access to the experimental values of the energy barriers and free‐energy difference for conformer interconversion in water solution has been elusive. Here, a new generation of fluorine‐containing glycomimetics is presented. We have applied a combination of organic synthesis, NMR spectroscopy and computational methods to investigate the conformational behaviour of idose‐ and glucose‐like rings. We have used low‐temperature NMR spectroscopic experiments to slow down the conformational exchange of the idose‐like rings. Under these conditions, the exchange rate becomes slow in the 19F NMR spectroscopic chemical shift timescale and allows shedding light on the thermodynamic and kinetic features of the equilibrium. Despite the minimal structural differences between these compounds, a remarkable difference in their dynamic behaviour indeed occurs. The importance of introducing fluorine atoms in these sugars mimics is also highlighted. Only the use of 19F NMR spectroscopic experiments has permitted the unveiling of key features of the conformational equilibrium that would have otherwise remained unobserved.